Classical Islamic philosophy and the gendered perfection of bodies and minds: engaging a complex discourse - De Rande, Raissa A. von Doetinchem (Body and religion, 2023)
How does classical Islamic philosophy envisage political leadership? Many - scholars and popular commentators alike - assume that, in line with certain Qur’anic and social commitments regarding gender roles, the Islamic political tradition is, and always has been, unenthusiastic about female political leadership. Examining the works of three important political thinkers - al-Farabi (d. 950), Ibn Tufayl (d. 1185), and Ibn Rushd (d. 1198) - this article complicates a simplistic vision. I will show that both on the issue of whether only the most perfect are capable of leadership and the question of whether women, too, can be such leaders, classical thinkers diverge and thus elude a simplistic assessment of the premodern tradition. My foray into classical Islamic discourses on political leadership will thus end by emphasizing caution. We must be wary of any attempts to draw straightforward connections between contemporary grievances and the classical tradition of Islamic political thought, as well as be attentive to the breadth and contestation of basic commitments among different figures.